The Effect of Learning Cell Strategy on Students’ Reading Comprehension of Narrative Text ( a study at the Eleventh Grade SMA Negeri 8 Padangsidimpuan in 2022/2023 Academic Year)” - Asriani Hasibuan; Rahmaini Paasaribu; Mawaddah Murni Gulo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
The purposes of this research are to know: 1) the application of learning cell strategy in teaching reading comprehension of narrative text, 2) the students’ reading comprehension before and after using learning cell strategy, 3) whether there is any significant effect of learning cell strategy on teaching reading comprehension of narrative text at the eleventh grade of SMA Negeri 8 Padangsidimpuan. This research used quantitative method with the pre-experimental research design by using one-group pretest and posttest design. The population of this research was all of the eleventh grade of SMA Negeri 8 Padangsidimpuan which consist of 83 students. the sample were XI MIA 2 which consist of 20 students which taken by purposive sampling. In collecting data the researcher used observation sheet and test and as instruments. The result of this research: 1) the application of learning cell strategy was 3.75, it was categorized “very good”. 2) the mean score of the students’ reading comprehension of narrative text was 49,5 and it was categorized “fail”. Meanwhile, after using learning cell strategy was 75,5, it is categorized “good”. 3) the result of data analysis showed that t-count>t-table (8.998>2.09). futhermore, the hypothesis was accepted. It means that there is a significant effect of learning cell strategy on students reading comprehension of narrative text at the eleventh grade of SMA Negeri 8 Padangsidempuan.